2014
DOI: 10.1111/php.12292
|View full text |Cite
|
Sign up to set email alerts
|

New Advances in Protection Against Solar Ultraviolet Radiation in Textiles for Summer Clothing

Abstract: Clothing is considered one of the most important tools for photoprotection against harmful solar ultraviolet radiation (UVR). The standard for sun-protective clothing is based on erythema despite other biological effects of UVR on the skin. We analyzed the potential protection against UVR in fabrics destined for summer clothing based on several action spectra. We examined 50 garments classified by type of fabric composition, structure of the fiber yarn and color. The ultraviolet protection factor was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In this study, woven cellulosic cotton fabric has been employed as a substrate because the cotton fabric is the most usual summer garments and has the slightest UV‐shielding ability. In this regard, many reports have been investigated to improve the UV protection properties of the cotton fabrics …”
Section: Resultsmentioning
confidence: 99%
“…In this study, woven cellulosic cotton fabric has been employed as a substrate because the cotton fabric is the most usual summer garments and has the slightest UV‐shielding ability. In this regard, many reports have been investigated to improve the UV protection properties of the cotton fabrics …”
Section: Resultsmentioning
confidence: 99%
“…However, it is of high demand to develop UV blocking textile products as most parts of the body are covered by textile clothing. Various studies have been conducted to prepare UV blocking fabric using white pigments [165,166,167,168,169,170,171,172]. Moreover, innovations in green technologies, development of multifunctional textile fabrics with self-cleaning properties, superhydrophobicity, antibacterial activity and UV blocking ability are emerging research fields in textiles and clothing industries.…”
Section: Superhydrophobic Textilesmentioning
confidence: 99%
“…In addition to considering the relevant light sources/doses, it can be useful to understand, as much as possible, the relationship between photostability and wavelength of light in order to ascertain whether the product would be particularly susceptible to degradation in certain lighting conditions. Clothing and/or bandages might be expected to provide some protection against light exposure, but light transmission through clothing could be considerable and there may also be restrictions suggested that disallow clothing or bandages because of concerns that the product would be absorbed or removed by these materials, thus limiting therapeutic benefit …”
Section: Relevant Light Sourcesmentioning
confidence: 99%
“…Clothing and/or bandages might be expected to provide some protection against light exposure, but light transmission through clothing could be considerable and there may also be restrictions suggested that disallow clothing or bandages because of concerns that the product would be absorbed or removed by these materials, thus limiting therapeutic benefit. 61,62 In the following sections, we will consider how the implications of topical product light exposure translate to photostability testing and risk mitigation strategies for the various common topical product types.…”
Section: Relevant Light Sourcesmentioning
confidence: 99%